2022
DOI: 10.3390/bs12030075
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Gender Stereotypes in the Network of Cognitive Abilities, Self-Perceived Ability and Intrinsic Value of School in School Children Depending on Sex and Preferences in STEM

Abstract: Adolescents face many barriers on the path towards a STEM profession, especially girls. We examine the gender stereotypes, cognitive abilities, self-perceived ability and intrinsic values of 546 Russian school children from 12 to 17 years old by sex and STEM preferences. In our sample, STEM students compared to no-STEM have higher cognitive abilities, intrinsic motivation towards math and science, are more confident in their math abilities and perceive math as being easier. Boys scored higher in science, math … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Perceived Difficulty of Math (subscale of a questionnaire used in "Gender stereotypes and incremental beliefs about STEM") (Ismatullina et al, 2022). This subscale is used to identify difficulties associated with the study of mathematics reported by adolescents.…”
Section: Instrumentsmentioning
confidence: 99%
“…Perceived Difficulty of Math (subscale of a questionnaire used in "Gender stereotypes and incremental beliefs about STEM") (Ismatullina et al, 2022). This subscale is used to identify difficulties associated with the study of mathematics reported by adolescents.…”
Section: Instrumentsmentioning
confidence: 99%
“…In recent years, due to the CP algorithm being able to detect overlapping symptoms that belong to multiple communities, the CP algorithm has been used to investigate psychological networks of depression and anxiety (Blanken et al, 2018;Kaiser, Herzog, Voderholzer, & Brakemeier, 2021), semantic memory (Cosgrove, Kenett, Beaty, & Diaz, 2021), emotions (Lange & Zickfeld, 2021), cognitive ability (Ismatullina, Adamovich, Zakharov, Vasin, & Voronin, 2022), aphasia (Ashaie & Castro, 2021), among others (Martarelli, Bertrams, & Wolff, 2021). However, the performance of the CP algorithm to identify nodes belonging to multiple communities in psychological data has not been evaluated by simulation studies.…”
Section: Performance Of the Cp Algorithm In Psychological Networkmentioning
confidence: 99%